Edukasi Keselamatan dan Kesehatan Kerja (K3) pada Siswa - Siswi SMK N 7 Semarang - Sutarno Sutarno; Diah Rahmawati; Galih Widyarini (Jurnal Pengabdian KOLABORATIF, 2024)
After graduating, many vocational school students take part directly in the work. One of them is vocational school students majoring in construction who can immediately work in the world of construction or projects. In the implementation of construction, many work accidents occur which are caused by human factors, because of understanding of the dangers in construction projects. It was recorded by the Social Security Administering Agency (BPJS) for Employment that from January to November 2022 there have been 265,334 work accidents in Indonesia. Therefore, students need to be given education about Occupational Health and Safety (K3). The aim is for the graduate to always apply K3 during construction so that graduates do not experience work accidents. Education was carried out through the presentation of material about K3 by the USM PKM team and continued with a question and answer session. Participants were very enthusiastic about participating in educational activities. It was shown from a lack of participants who asked questions to the PKM team. Apart from that, the results showed that 81% of the students thought that the PKM material was in line with community needs and that the overall PKM activities provided benefits.